2016
DOI: 10.1021/acsami.6b05698
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Mechanical Properties of Biodegradable Polymer Blends Using Tubular Nanoparticle Stitching of the Interfaces

Abstract: "Green" polymer nanocomposites were made by melt blending biodegradable poly(lactic acid) (PLA) and poly(butylene adipate-co-butylene terephthalate) (PBAT) with either montmorillonite clays (Cloisite Na(+)), halloysite nanotubes (HNTs), the resorcinol diphenyl phosphate (RDP)-coated Cloisite Na(+), and coated HNTs. A technique for measuring the work of adhesion (Wa) between nanoparticles and their matrixes was used to determine the dispersion preference of the nanoparticles in the PLA/PBAT blend system. Transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 42 publications
4
46
0
Order By: Relevance
“…Given that the aspect ratio of exfoliated clay platelets could be several magnitudes larger than that of clay tactoids, it is easier for the micro-cracks to enlarge and propagate under external stress in the exfoliated polymer/clay blend. Moreover, a similar result was also found in binary polymer blends with clay [47]. When C-Na + , C-RDP clay and C-30B clay were added to a biodegradable PLA/poly(butylene adipate-co-butylene terephthalate) (PBAT) blend, C-30B performs best in reducing the domain size and increasing compatibility between two polymers, as can be seen in Figure 9.…”
Section: Physical Properties 41 Impact Resistancesupporting
confidence: 68%
See 1 more Smart Citation
“…Given that the aspect ratio of exfoliated clay platelets could be several magnitudes larger than that of clay tactoids, it is easier for the micro-cracks to enlarge and propagate under external stress in the exfoliated polymer/clay blend. Moreover, a similar result was also found in binary polymer blends with clay [47]. When C-Na + , C-RDP clay and C-30B clay were added to a biodegradable PLA/poly(butylene adipate-co-butylene terephthalate) (PBAT) blend, C-30B performs best in reducing the domain size and increasing compatibility between two polymers, as can be seen in Figure 9.…”
Section: Physical Properties 41 Impact Resistancesupporting
confidence: 68%
“…For binary polymer systems, the morphology of the polymer phase separation and filler location play a significant role in the rheological response. In previous section, Guo, et al [47,56] showed that the addition of C-30B and C-RDP could effectively increase the compatibility between PLA and PBAT, while reducing the impact strength due to the strong barrier effect at the polymer interface. HNTs and H-RDP were not as effective at reducing the domain size and increasing the polymer compatibility, but the impact strength was enhanced with the "stitching" effect of nanotubes.…”
Section: Flame Retardantsmentioning
confidence: 98%
“…The interfacial tension between the two polymers can be then determined via the Young's equationγpcdtbt=γpscosθ + γinterwhere γ pcdtbt and γ ps are, respectively, the surface tensions of PCDTBT and PS, γ inter is the interfacial tension, and θ is Young's contact angle between PCDTBT and PS. γ pcdtbt and γ ps were first measured as a function of temperature using the two‐liquid (water and diiodomethane) contact angle method, where the surface tension of a given polymer can be computed by using the measured θ of polar (i.e., water) and nonpolar (i.e., diiodomethane) liquids on the polymer thin film. γ pcdtbt and γ ps for varying PS MW (from 50K to 7M Da) were determined at five different temperature points (between 20 °C and ≈50 °C) and linearly extrapolated to higher temperatures as shown in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of water-soluble polymers are available as sacrificial polymers, such as polyvinyl alcohol (PVA), 10,11 poly(ethylene oxide), [12][13][14] polyvinylpyrrolidone, 15 and sulfopolyester 16,17 to avoid any toxicity problem during the process. Nanoparticles give polymer materials additional properties (e. g., electrical, 18,19 mechanical, 20,21 flame retardant, 22,23 and antimicrobial 24,25 ). The porous material has a high specific surface area, and the internal structure is an ideal host for the integration of these nanoparticles.…”
Section: Introductionmentioning
confidence: 99%